Regional differences in cell‐mediated immunity in people with diabetic peripheral neuropathy. Issue 2 (10th October 2019) - Pickwell, K.; Geerts, M.; van Moorsel, D.; Hilkman, D.; Kars, M.; Schaper, N. C.
Abstract: Aim: To study cell‐mediated immunity in the feet of people with type 2 diabetes with polyneuropathy. Methods: In a cohort comprising people with type 2 diabetes with polyneuropathy ( n = 17) and without polyneuropathy ( n = 12) and a healthy control group ( n = 12) indurations due to delayed‐type hypersensitivity responses to intracutaneous Candida albicans antigen were determined in the foot and compared with those in the arm (an area relatively spared in diabetic polyneuropathy). The sizes of indurations on the foot were correlated with electromyographic measurements in the participants with diabetes. Results: No differences were observed in the median size of indurations between the foot and arm in healthy controls and participants without polyneuropathy; in participants with polyneuropathy, induration sizes on the foot were smaller than on the arm: 0 (95% CI 0 to 1) vs 5 (95% CI 2 to 6) mm ( P < 0.01). In participants with diabetes, larger indurations correlated with better nerve function (Spearman's rho 0.35 to 0.39). Conclusion: Our findings suggest that diabetic peripheral polyneuropathy negatively affects cell‐mediated immunity in the foot. (Clinical Trials registry no.: NCT01370837) What's new?: Local immune responses can be impaired as a result of neurological deficits. Diabetic peripheral neuropathy could negatively affect cell‐mediated immunity selectively in the foot, the site most frequently and severely affected by peripheral neuropathy. More severe impairment of cell‐mediated immunity correlates with worse peripheral nerve function as measured by electromyography. Our study is the first to suggest the presence of locally diminished cell‐mediated immunity in the foot in people with diabetic peripheral neuropathy. Impaired cellular immunity in the foot may explain the paucity of signs of inflammation in diabetic foot infections.